Antisocial Personality Disorder Experienced by Igor Malev, The Main Character In Paulo Coelho's Novel The Winner Stands Alone(2009): An Abnormal Psychology - Afandi, Ibnu Rosid; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
The problem of this study "How is the antisocial personality disorder (ASDP) reflected in Paulo Coelho The Winner Stands Alone Novel (2009). The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on Abnormal Psychology. The researcher employs qualitative method. In this method, the writer uses two data sources; primary and secondary. The primary data source is the novel itself. The secondary data sources are the books about abnormal pyschology and other sources, which are related to the analysis, such as official website, related theories. The method of data collection is library research and technique of data collection is descriptive and hermeneutic technique. Based on the analysis, the researcher draws conclusions as follows: The first is based on structural elements which consist of ; character and charcterization, plot, setting, point of view, style and theme. Those elements make unity and coherence. So that they form an artistic novel. The second is based on abnormal psychology, Igor Malev has experienced personality disturbance called antisocial personality disorder. The symptoms of this disorder according to DSM-IV TR and ICD-10 are ;1) deception, as indicated by repeatedly lying, use of aliases, or conning others for personal profit or pleasure;2) irritability and aggressiveness, as indicated by repeated physical fights or assaults; lack of remorse, as indicated by being indifferent to or rationalizing having hurt;3) callous unconcern for the feelings of others. The causes of ASPD which happened to Igor Malev were social and psychological factors. He experienced sad childhood and also unworthy war in Afghanistan.